Pembuatan BAK Sampah Beton di Pantai Jerman, Kabupaten Badung, Bali - I Ketut Nuraga; Ananda Putra, I Gusti Agung (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
In an effort to address the waste issue in Badung Regency, particularly in the tourist area of German Beach, PSU Undiknas partnered with Coca Cola to construct concrete waste bins. This initiative aimed to raise public awareness about the hazards of waste pollution. The methods of implementing this service activity are as follows: (1) Conducting socialization to German Beach residents to convey the activity plan for Making Concrete Garbage Tubs, (2) Identifying work items carried out in addition to making landfills also carried out site cleaning from scattered garbage, (3) Mobilization of equipment used for making concrete garbage bins, (4) Holding materials in the form of coral,  sand, cement, adobe and concrete iron for garbage bin making work, (5) Installation of bricks as high as 1.0 m length 2.0 m, width 1.0 m, (6) Floor work with concrete rebates, (7) Plastering and aci work on all surfaces of adobes, (8) Roof work is carried out with formwork, ironing and cast concrete. The implementation of making concrete trash cans resulted in 3 permanent trash cans, which are located in the middle of the German Beach environment. In one permanent tub made there are three partitions for organic, inorganic, and B3 waste.